Pakhtunwali and Its Elements: An Analysis of the Representation of Pakhtun Women in Pakistan - Abu Hurara (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Women in Pakhtunwali are entitled to the claim they act and believe in, to the names they bear, and to the manifested position they exercise, both as body and gender. This study place the manifestation of Pakhtun women into the context of Pakhtunwali with a concrete analysis of its elements. This research is mainly concerned with gender relations and socialized patterns of Pakhtun’s women in Pakhtunwali. It takes up three overlapping sets of issues. First, it sets to bring into a vivid illustrations of the existing debate about Pakhtunwali and its elements and practice. Secondly, it explores gender categorization of Pakhtuns (especially women) into groups. Thirdly, it builds on the first two by addressing assumptions about the gender segregation by questioning the presupposition of the manifestation of Pakhtun women. This research employs qualitative methods, a multidisciplinary approach, and historical methodology to analyze various theories, including the historical evolution and origin of the Pakhtun theory as well as sociological and anthropological models of Pakhtun kinship-based tribal systems. It contributes to existing literature on Pakhtunwali by addressing the underexplored representation of Pakhtun women in terms of gender relations and socialized patterns, patriarch values, and gender categories. The article identifies knowledge gaps and provides a new interpretation of Pakhtunwali, revealing that historical discourse has largely overlooked the dichotomy of interior and exterior between Pakhtun men and women, interpreting women’s contributions quite subjectively in nature and patriarchal in practice, thereby offering a theoretical understanding of gender representation in Pakhtunwali.